Bevacizumab-mediated tumor vasculature remodelling improves tumor infiltration and antitumor efficacy of GD2-CAR T cells in a human neuroblastoma preclinical model. (2nd January 2018) - Bocca, Paola; Di Carlo, Emma; Caruana, Ignazio; Emionite, Laura; Cilli, Michele; De Angelis, Biagio; Quintarelli, Concetta; Pezzolo, Annalisa; Raffaghello, Lizzia; Morandi, Fabio; Locatelli, Franco; Pistoia, Vito; et al.
ABSTRACT: GD2-redirected chimeric antigen receptor (CAR) T lymphocytes represent a promising therapeutic option for immunotherapy of neuroblastoma (NB). However, despite the encouraging therapeutic effects observed in some hematological malignancies, clinical results of CAR T cell immunotherapy in solid tumors are still modest. Tumor driven neo-angiogenesis supports an immunosuppressive microenvironment that influences treatment responses and is amenable to targeting with antiangiogenic drugs. The latter agents promote lymphocyte tumor infiltration by transiently reprogramming tumor vasculature, and may represent a valid combinatorial approach with CAR T cell immunotherapy. In light of these considerations, we investigated the anti-NB activity of GD2-CAR T cells combined with bevacizumab (BEV) in an orthotopic xenograft model of human NB. Two weeks after tumor implantation, mice received BEV or GD2-CAR T cells or both by single intravenous administration. GD2-CAR T cells exerted a significant anti-NB activity only in combination with BEV, even at the lowest concentration tested, which per se did not inhibit tumor growth. When combined with BEV, GD2-CAR T cells massively infiltrated tumor mass where they produced interferon-γ (IFN-γ), which, in turn, induced expression of CXCL10 by NB cells. IFN-γ,  and possibly other cytokines, upregulated NB cell expression of PD-L1, while tumor infiltrating GD2-CAR T cells expressed PD-1. Thus, the PD-1/PD-L1 axis can limit the anti-tumor efficacy of the GD2-CAR T cell/BEV association. This study provides a strong rationale for testing the combination of GD2-CAR T cells with BEV in a clinical trial enrolling NB patients. PD-L1 silencing or blocking strategies may further enhance the efficacy of such combination.